Nitrogen cycling activities during decreased stratification in the coastal oxygen minimum zone off Namibia - Vuillemin, Aurèle (Frontiers in Microbiology, 2023)
Productive oxygen minimum zones are regions dominated by heterotrophic denitrification fueled by sinking organic matter. Microbial redox-sensitive transformations therein result in the loss and overall geochemical deficit in inorganic fixed nitrogen in the water column, thereby impacting global climate in terms of nutrient equilibrium and greenhouse gases. Here, geochemical data are combined with metagenomes, metatranscriptomes, and stable-isotope probing incubations from the water column and subseafloor of the Benguela upwelling system. The taxonomic composition of 16S rRNA genes and relative expression of functional marker genes are used to explore metabolic activities by nitrifiers and denitrifiers under decreased stratification and increased lateral ventilation in Namibian coastal waters. Active planktonic nitrifiers were affiliated with Candidatus Nitrosopumilus and Candidatus Nitrosopelagicus among Archaea, and Nitrospina, Nitrosomonas, Nitrosococcus, and Nitrospira among Bacteria. Concurrent evidence from taxonomic and functional marker genes shows that populations of Nitrososphaeria and Nitrospinota were highly active under dysoxic conditions, coupling ammonia and nitrite oxidation with respiratory nitrite reduction, but minor metabolic activity toward mixotrophic use of simple nitrogen compounds. Although active reduction of nitric oxide to nitrous oxide by Nitrospirota, Gammaproteobacteria, and Desulfobacterota was tractable in bottom waters, the produced nitrous oxide was apparently scavenged at the ocean surface by Bacteroidota. Planctomycetota involved in anaerobic ammonia oxidation were identified in dysoxic waters and their underlying sediments, but were not found to be metabolically active due to limited availability of nitrite. Consistent with water column geochemical profiles, metatranscriptomic data demonstrate that nitrifier denitrification is fueled by fixed and organic nitrogen dissolved in dysoxic waters, and prevails over canonical denitrification and anaerobic oxidation of ammonia when the Namibian coastal waters and sediment–water interface on the shelf are ventilated by lateral currents during austral winter.